2006
DOI: 10.1007/s00403-006-0719-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus: a genetic epidemiology study of 695 patients from China

Abstract: Our purpose was to explore potential genetic models for systemic lupus erythematosus (SLE) and analyze genetic epidemiologic characteristics of SLE in a Chinese population. Data for 695 patients with SLE were obtained by using a uniform questionnaire. Patients, clinical characteristics and their family history were analyzed using software. A complex segregation analysis was conducted to propose potential genetic models for SLE. The mean +/- SD age of onset were 30.2 +/- 10.5 years and mean time to progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 28 publications
3
28
1
Order By: Relevance
“…This finding opposes that of Wang et al 22 in a study of 695 Chinese patients with SLE where they observed photosensitivity in 16.3% of late-onset and 29.3% of early-onset SLE cases. These differences are probably due to race, as our population has <2% Asian composition.…”
Section: Discussioncontrasting
confidence: 98%
“…This finding opposes that of Wang et al 22 in a study of 695 Chinese patients with SLE where they observed photosensitivity in 16.3% of late-onset and 29.3% of early-onset SLE cases. These differences are probably due to race, as our population has <2% Asian composition.…”
Section: Discussioncontrasting
confidence: 98%
“…SLE is a prototypic systemic autoimmune disease characterized by autoantibody production, complement activation, and tissue and organ damage [30] and influenced by both genetic and environmental factors [31]. Severity, risk and clinical manifestation of SLE were varied by race, geography and sex [32][33][34][35].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…13 For example, there have been notable successes in genome-wide searches 14 for susceptibility loci for breast cancer (heritability ~25%), lung cancer (26%), Type 2 diabetes mellitus (26%), Parkinson’s disease (34%), multiple sclerosis (41%), systemic lupus erythematosus (44%) and age-related macular degeneration (46%). 1520 …”
Section: Introductionmentioning
confidence: 99%